Separation and determination of microRNAs by high‐speed capillary sieving electrophoresis. Issue 20 (5th September 2018) - Wang, Wei; Cai, Xiaoyu; Lin, Ping; Bai, Ruiguang
Abstract: In this work, high‐speed capillary sieving electrophoresis with laser‐induced fluorescence detection was applied to simultaneously determine three microRNAs. A developed manual sample introduction device for the high‐speed capillary electrophoresis system was applied to perform sample injection. Strategies, including field‐amplified sample injection and electrokinetic injection, were studied to improve the detection sensitivity. Under the optimal conditions, the limit of detection for DNA‐159 could be lowered to 5.10 × 10 −12  mol/L. In order to achieve enough separation resolution, two DNA probes were designed to have extra sequences that acted as the drag tails. Under the optimized conditions, the three DNA probes and the complexes of microRNA‐156, microRNA‐159, and microRNA‐166 could be completely separated within 3.2 min in background electrolyte (pH 8.7) containing 2.0% m/m polyvinyl pyrrolidone and 0.4% m/m hydroxyethyl cellulose. The limits of detection for the three microRNAs were 0.051, 0.11, and 0.25 nmol/L, respectively. Then the method was applied to analyze the microRNAs spiked in the samples extracted from banana leaves. The recoveries ranged from 114.3 to 121.1% (n = 3). The results showed that the method developed in this work was an effective means for microRNA assay.